2023
DOI: 10.3390/microorganisms11040884
|View full text |Cite
|
Sign up to set email alerts
|

Viral Identification Using Multiplex Polymerase Chain Reaction Testing Does Not Reduce Antibiotic Prescribing in Paediatric Intensive Care Units

Abstract: PCR tests for viral identification, performed on nasopharyngeal secretions, have experienced a major boom in the last few years. Their use is very frequent, but their indications are still not well defined, especially in Paediatric Intensive Care Units (PICU). These tests are used for the microbiological diagnosis of lower respiratory infections but can be used in other situations. The aim of the study was to investigate the effect of viral identification on antibiotic therapy management. We conducted a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…One possible explanation for this may be differences in the indication for testing of children in the ED versus later during their clinical course in the ICU or inpatient floors. 25 Overall, these data suggest that respiratory coinfections in children with SARS-CoV-2 are common, and they are most often observed in young children presenting to the ED.…”
Section: Discussionmentioning
confidence: 80%
“…One possible explanation for this may be differences in the indication for testing of children in the ED versus later during their clinical course in the ICU or inpatient floors. 25 Overall, these data suggest that respiratory coinfections in children with SARS-CoV-2 are common, and they are most often observed in young children presenting to the ED.…”
Section: Discussionmentioning
confidence: 80%
“…Also, El-Nawawy et al reported that BioFire was associated with a 33.3% increase in positive specimens when compared to conventional methods [14]. Hayotte et al found that at least one target was identified by BPPP in (70%) of patients [15]. Positive BioFire results with negative bacterial culture may be related to multiple factors: low count of the isolate on culture plates compared to the cut-off which is therefore not reported, unavailability of culture media that support growth of fastidious bacteria, PCR may detect non-viable organisms, in addition to the antibiotic misuse which may inhibit growth on culture media, also the fact that the count released by BioFire is in the form of copies/ml which is greater when compared to the culture count in the form of CFU/ml [16].…”
Section: Pathogens Detected Using Biofire Filmarraymentioning
confidence: 99%
“…Similarly, El-Nawawy et al found that HR/EV was the most frequently detected virus (n=21, 29.2%) followed by RSV (n=19, 26.4), Influenza A (n=8;11.1) and Adenovirus (n=7, 9.7%) [14]. Also, Hayotte and his colleagues reported that Human Rhinovirus (n=215,56%) and RSV(n=106, 28%) were the two predominant targets identified by BioFire followed by Adenovirus (n=55, 14%), Parainfluenza (n=48, 13%), Human metapneumovirus (n=25, 7%), Influenza (n=26, 7%) and Coronavirus (n=24, 6%) [15]. This can be due to the decreased RSV infections owing to Palivizumab prophylaxis [20].…”
Section: Pathogens Detected Using Biofire Filmarraymentioning
confidence: 99%
See 1 more Smart Citation